A novel PLS1 c.981+1G>A variant causes autosomal‐dominant hereditary hearing loss in a family. Issue 4 (12th January 2023) - Xu, Liangpu; Wang, Xinrui; Li, Jia; Chen, Lingji; Wang, Haiwei; Xu, Shiyi; Zhang, Yanhong; Li, Wei; Yao, Pengcheng; Tan, Meihua; Zhou, Si; Chen, Meihuan; et al.
Abstract: The fimbrin protein family contains a variety of proteins, among which Plastin1 (PLS1) is an important member. According to recent studies, variations in the coding region of the PLS1 gene are associated with the development of deafness. However, the molecular mechanism of deafness caused by PLS1 gene variants remains unknown. Whole‐exome sequencing was performed on hearing‐impaired family members and hearing family members to identify pathogenic variants, followed by Sanger sequencing. A minigene assay was conducted to investigate the effect of the variant on PLS1 mRNA splicing. The pathogenicity of the variant was further investigated in zebrafish. RNA‐sequencing (RNA‐seq) was performed to analyze the dysregulation of downstream signaling pathways caused by knockdown of PLS1 expression. We identified a novel variant, PLS1 c.981+1G>A, in a large Chinese family with hearing loss and showed that the variant is responsible for the occurrence of hearing loss by inducing exon 8 skipping. The variant caused abnormal inner ear phenotypes, characterized by decreases in the mean otolith distance, anterior otolith diameter, posterior otolith diameter, cochlear diameter, and swimming speed and distance in zebrafish. Furthermore, silencing PLS1 expression significantly upregulated the expression of genes in the PI3K‐Akt signaling pathway, including Col6a3, Spp1, Itgb3 and hepatocyte growth factor ( Hgf ). PLS1 c.981+1G>A is a novel pathogenic variant causing hearing loss by inducing exon 8 skipping. Upregulation of the expression of genes in the PI3K‐Akt signaling pathway plays an important role in the pathogenesis caused by variants in the PLS1 gene. Abstract :